TINJAUAN PENANGANAN LIMBAH MEDIS PADAT BAHAN BERBAHAYA BERACUN PADA KEGIATAN VAKSINASI COVID - 19 DI PUSKESMAS CARINGIN BOGOR PADA TAHUN 2022 - Budiman, Ferry; Bambang Purnama, Lubis (Jurnal Sanitasi Profesional Indonesia, 2022)
The increasing spread of the Covid - 19 virus has led to an increase in the amount of medical waste that is categorized as B3 solid waste. The handling of Covid - 19 medical waste, especially those produced by health service facilities, must be managed and destroyed in accordance with the procedures and technical requirements for handling B3 waste. According to Law no. 22 of 2021 concerning the Implementation of Environmental Protection and Management strictly stipulates that processing B3 waste is a process of reducing and/or eliminating hazardous or toxic properties. The purpose of this study was to determine the handling of B3 solid medical waste in the Covid-19 vaccination activity. Jemis is an observational descriptive research using primary data by weighing medical waste, interviews and observations using questionnaires, observation sheets and scales. The results of research on handling solid medical waste at the sorting stage are 100% eligible, the container stage is 25% not eligible, the in-situ transportation stage is 33% not eligible, ex-situ transportation is 100% eligible and temporary storage is 50% not eligible. Facilities and infrastructure at the sorting stage are 100% eligible, container is 100% eligible, transportation is 100% not meeting the requirements and temporary storage is 64% not fulfilling the requirements. Knowledge of medical staff was categorized as good (87%) and sufficient (13%), knowledge of cleaning staff was categorized as good 86%, sufficient 7% categorized, and 7% less categorized.